Intravenous tirofiban following successful reperfusion in intracranial large artery atherosclerotic stroke: A secondary analysis of a randomized clinical trial - Jiacheng Huang; Weilin Kong; Chang Liu; Jiaxing Song; Jie Yang; Chengsong Yue; Linyu Li; Jinrong Hu; Yan Tian; Zhouzhou Peng; Changwei Guo; Dahong Yang; et al. (Annals of Clinical and Translational Neurology, 2023)
Abstract Objective This study aimed to investigate whether treatment with adjunct intravenous tirofiban is associated with improved outcomes following successful reperfusion in patients with intracranial atherosclerotic stroke. Methods Patients with intracranial large artery atherosclerotic (LAA) stroke and an expanded Treatment in Cerebral Ischemia angiographic score of 2b50 to 3 from the Effect of Intravenous Tirofiban versus Placebo Before Endovascular Thrombectomy on Functional Outcomes in Large Vessel Occlusion Stroke (RESCUE BT) trial were included. The primary outcome was the difference in proportion of independent functional outcome (modified Rankin score of 0–2 at 90 days). Safety outcomes included the rates of symptomatic intracranial hemorrhage (sICH) and 90‐day mortality. Results Among the 382 patients with intracranial LAA stroke and successful reperfusion, 175 patients (45.8%) were treated with intravenous tirofiban and 207 (54.2%) with placebo. The proportion of patients with independent functional outcome at 90 days was 54.3% (95 out of 175) with tirofiban and 44.0% (91 out of 207) with placebo (adjusted odds ratio [aOR], 1.58; 95% CI, 1.02–2.44; p = 0.04). Intravenous tirofiban was not significantly associated with an increased risk of sICH (12/175 [6.9%] vs. 11/207 [5.3%]; aOR, 1.41; 95% CI, 0.59–3.34; p = 0.44) or 90‐day mortality (21/175 [12.0%] vs. 34/207 [16.4%]; aOR, 0.71; 95% CI, 0.38–1.31; p = 0.27). Interpretation Among patients with acute intracranial LAA stroke and successful reperfusion following endovascular thrombectomy, adjunct intravenous tirofiban was associated with a higher rate of independent functional outcome, without higher rates of sICH or mortality. Confirmatory randomized trials in these patients are desirable.